2023
DOI: 10.3389/fphys.2023.1110526
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual cycle and hormonal contraceptive phases’ effect on elite rowers’ training, performance and wellness

Abstract: Objectives: To investigate the effect of menstrual cycle (MC) and hormonal contraception (HC) phases in elite rowers training, performance and wellness monitoring.Methods: Twelve French elite rowers were follow-up for 4,2 cycles on average in their final preparation for the Olympics and Paralympics Games in Tokyo 2021 through an on-site longitudinal study based on repeated measures. Daily self-reported evaluation using Likert rating scales of wellness (sleep quality, fitness, mood, injuries’ pain), menstrual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Yet, the increased trend in the intensity index in the most intensive effort displayed by the OC-users during the pills' taking phase should be further investigated. In addition, previous studies showed that the OC-users evaluate their training performance lower during the withdrawal phase ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, the increased trend in the intensity index in the most intensive effort displayed by the OC-users during the pills' taking phase should be further investigated. In addition, previous studies showed that the OC-users evaluate their training performance lower during the withdrawal phase ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the internal load variables, the heart rate was collected through heart rate monitors. The RPE, was collected after each training session using and application previously described ( 17 ), according to the BORG scale CR10 ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The testing sessions were organized without taking into consideration the menstrual cycle. Indeed, Antero et al ( 32 ) highlight variations in performance between the periods of the menstrual cycle and differences in performance between players who have contraception compared with those who do not. We, therefore, suggest that future studies should consider the timing of the menstrual cycle to avoid misleading results or the lack of a training-induced effect.…”
Section: Discussionmentioning
confidence: 99%
“…In women taking combined contraceptive pills (mono-, bi-, tri-, or quadriphasic oral contraceptives) the exogenous hormones are fairly constant and reduce the endogenous levels of sex hormones, followed by a phase without exogenous hormones during pill withdrawal. These sex hormone fluctuations impact numerous physiological functions that may influence training [ 160 , 161 ] and performance [ 162 , 163 ], such as recovery [ 164 ], wellness [ 165 ], and in particular, considering the altitude environment, respiratory function [ 166 ].
Fig.
…”
Section: Impact Of Hormonal Changesmentioning
confidence: 99%